The Influence of Service Quality and Customer Perceived Value on Intention to Purchase Sacrificial Animals with Customer Satisfaction as a Mediating Variable at Magribi Farm - Juliyanto Juliyanto; Ari Setiawan (Eduvest - Journal of Universal Studies, 2025)
The failure to achieve sacrificial animal sales targets at Magribi Farm—with only 60% of targets met from 2022 to 2024—poses significant challenges, including unmet profit targets and increasing operational costs. This study investigates how service quality and customer perceived value influence purchase intention for sacrificial animals, with customer satisfaction as a mediating variable. Using a quantitative cross-sectional approach, data were collected from 135 Magribi Farm customers through structured questionnaires and analyzed using structural equation modeling (SEM) with LISREL software. Results indicate that service quality significantly affects customer perceived value (, ). Both service quality and customer perceived value positively influence customer satisfaction (coefficients = 0.37 and 0.55, respectively) and purchase intention (coefficients = 0.21 and 0.33, respectively). Customer satisfaction also significantly mediates the relationship between service quality, customer perceived value, and purchase intention. These findings provide actionable insights for improving service delivery and marketing strategies in the sacrificial animal industry, emphasizing the critical roles of service excellence and value creation in driving customer satisfaction and purchase behavior.